Howard Gardner’s Multiple Intelligences Theory in the Paradigm Transformation of Islamic Educational Psychology - Syafiq, Ahmad; Rohimah, Siti (El-Rusyd, 2026)
This study examines the paradigm transformation of intelligence from the concept of Intelligence Quotient (IQ) to Howard Gardner’s Multiple Intelligences (MI) within the perspective of Islamic Educational Psychology. The purpose of this research is to analyze the shift in the concept of intelligence and to integrate it with Islamic educational values. A qualitative approach was employed, using library research and content analysis techniques. Data sources were drawn from primary and secondary literature relevant to intelligence theory and Islamic education. The findings reveal that the Intelligence Quotient (IQ) paradigm is limited and reductionist, as it emphasizes only cognitive aspects. In contrast, the Multiple Intelligences theory provides a broader and multidimensional understanding of human intelligence. From an Islamic perspective, intelligence encompasses not only intellectual aspects but also the dimensions of reason (‘aql), heart (qalb), and spirit (ruh), all oriented toward servitude to Allah SWT. The integration of Multiple Intelligences with Islamic education produces a holistic, humanistic, and transcendental paradigm of intelligence. In conclusion, the transformation of the intelligence paradigm demonstrates a shift from a single-dimensional approach to a multidimensional framework aligned with Islamic values in shaping the concept of insān kāmil.